Psychometric Properties of the Brief Version of the Social Skills Inventory for Adolescents - Romera Leme, Vanessa Barbosa (2017)
The present study aimed to evaluate the evidence of internal structure and scores reliability of the Social Skills Inventory for adolescents - brief version (IHSA-Del-Prette). The following analyses were performed: (1) Exploratory Factor Analysis - EFA; (2) Confirmatory Factor Analysis - CFA; (3) Reliability; (4) Multigroup Analysis (invariance). The participants were 2,291 students of the Middle and High Schools, both sexes aged 12 to 17 years old divided into two sample groups: 1,172 participants in sample group 1 (collected 2006-2007) and 1,119 in sample group 2 (collected 2011-2012). The results of the EFA (group 1) support the four subscales structure (Self-control, Affective Approach, Empathy and Assertiveness) for 16 items (loadings > .30). The structure was confirmed by the CFA performed on the second group (CFI = .96, TLI = .95, RMSEA = .05, 90% CI [.04,.05], loadings > .50); and showed scalar invariance (samples 1 and 2) due to group and age, as well as partial scalar invariance due to gender (Delta CFI < .01; Delta NCI < .02). It was concluded the brief version of IHSA-Del-Prette presents psychometric properties for use in the Brazilian context.